Suppressing Interfacial Recombination with a Strong‐Interaction Surface Modulator for Efficient Inverted Perovskite Solar Cells. Issue 48 (30th October 2022) - Li, Bowei; Deng, Jun; Smith, Joel A.; Caprioglio, Pietro; Ji, Kangyu; Luo, Deying; McGettrick, James D.; Jayawardena, K. D. G. Imalka; Kilbride, Rachel C.; Ren, Aobo; Hinder, Steven; Bi, Jinxin; et al.
Abstract: Successful manipulation of halide perovskite surfaces is typically achieved via the interactions between modulators and perovskites. Herein, it is demonstrated that a strong‐interaction surface modulator is beneficial to reduce interfacial recombination losses in inverted (p‐i‐n) perovskite solar cells (IPSCs). Two organic ammonium salts are investigated, consisting of 4‐hydroxyphenethylammonium iodide and 2‐thiopheneethylammonium iodide (2‐TEAI). Without thermal annealing, these two modulators can recover the photoluminescence quantum yield of the neat perovskite film in contact with fullerene electron transport layer (ETL). Compared to the hydroxyl‐functionalized phenethylammonium moiety, the thienylammonium facilitates the formation of a quasi‐2D structure onto the perovskite. Density functional theory and quasi‐Fermi level splitting calculations reveal that the 2‐TEAI has a stronger interaction with the perovskite surface, contributing to more suppressed non‐radiative recombination at the perovskite/ETL interface and improved open‐circuit voltage ( V OC ) of the fabricated IPSCs. As a result, the V OC increases from 1.11 to 1.20 V (based on a perovskite bandgap of 1.63 eV), yielding a power conversion efficiency (PCE) from ≈20% to 21.9% (stabilized PCE of 21.3%, the highest reported PCEs for IPSCs employing poly[ N, N ′′‐bis(4‐butylphenyl)‐ N, N ′′‐bis(phenyl)benzidine] as the hole transport layer, alongside the enhanced operational and shelf‐life stability for unencapsulated devices. Abstract : The role of the surface modulator cannot simply be attributed to the passivation effect. Here, it is shown that the strong‐interaction surface modulator, 2‐thiopheneethylammonium iodide (2‐TEAI, is helpful in inverted (p‐i‐n) perovskite solar cells. Through forming a quasi‐2D structure and reconfiguring the electronic energy level of perovskite film, 2‐TEAI contributes to the reduced interfacial recombination losses, and enhanced device performance.